DINAMIKA KOMUNIKASI POLITIK ISLAM DALAM RUANG PUBLIK DIGITAL: KAJIAN ISU SYARIAT ISLAM ACEH DI TIKTOK - Hasmuni Hasmuni; Rizqi Wahyudi (LPPM Stikosa - AWS, 2025)
This study investigates how debates on Syariat Islam in Aceh have shifted from formal religious spaces into TikTok’s fast-paced, visual, and algorithmically curated environment. Using a digital ethnographic case study, the research analyzes a selection of TikTok videos and comment interactions produced by ulama, journalists, activists, political actors, and ordinary citizens to understand how Islamic political communication is constructed and contested in everyday digital life. Through reflexive thematic analysis, five key dynamics emerge: Syariat Islam as a moral identity that is both affirmed and problematized; tensions involving justice, gender, and political use of religious norms; humor and satire as subtle forms of critique; shifting religious authority from traditional scholars to digitally influential creators; and the strong role of algorithmic amplification in shaping public perception. The findings enrich theoretical perspectives on the digital public sphere, mediatized religion, and media ecology by illustrating how religious meaning is increasingly shaped by visual performance, emotional engagement, and platform logic. Practically, the study highlights the need for policymakers, religious institutions, and dakwah organizations in Aceh to adopt communication strategies that are adaptive, dialogic, and digitally literate. It also opens pathways for future research across platforms and deeper methodological